Hubungan Tingkat Kecemasan dengan Kejadian Sindrom Dispepsia pada Pasien di Rumah Sakit Annisa Tangerang - Prida Sahla Rizkiyyah; Rangga Saputra; M. Martono Diel (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Dyspepsia is one of the top digestive disorders that are often found in society. The symptoms that arise include pain or discomfort in the heartburn, stomach feels full, nausea, vomiting, satiety, quickly, and often burping. This condition is not only influenced by organic factors, but also closely related to psychosomatic factors, one of which is anxiety. Anxiety can trigger an increase in the hull of stomach acid secretion, motility disorder, as well as a decrease in stomach mucosa function, which exacerbates in dyspepsia symptoms. This study aims to determine the relationship between anxiety levels and the incidence of spsia syndrome in patients at Annisa Tangerang Hospital. This study used quantitative designs with a correlational approach and a cross sectional design. The total population was taken from the last 3 months patient data and the number of samples using the slovin formula with a result of 130 respondents chosen with accidental sampling technique. The research instrument in the form of anxiety-level questionnaire and symptoms questionnaire. The data were analyzed using the Chi Square test with a significance level of p <0.05. The results showed a meaningful connection between anxiety levels and the incidence of dyspepsia syndrome (p = 0.005). This finding is in line with previous research that confirms that psychological factors can worsen digestive condition. The conclusion of this study is that anxiety has an important contribution to the emergence of dyspeptic syndrome. Therefore, the arrangement of patients based on dyspepsia needs to be carried out thoroughly, not only through pharmacological therapies, but also through nursing interventions that pay attention to the patient's psychological aspects. The results of this study are expected to be input for health workers, educational institutions, and subsequent researchers to develop holistic management strategies in reducing the incidence of dyspepsia.